The trend of consumption pattern among college students in Malang city - Rany Adelina (Berita Kedokteran Masyarakat (BKM), 2018)
This study was conducted to know the trend of consumption pattern of the college student in Malang city. This case-case study with 397 participants was recruited voluntarily. Participants were given the FFQ (Food Frequency Questionnaire) questionnaire containing 10 categories including staple foods, vegetables, fruits, meat, fast food, fish, beans, dairy products, drinks, and supplements. There were six frequencies assessed in this study such as' more than 1 times a day ',' 1 times a day ',' 4-6 times a week ',' 1-3 times a week ',' 1-3 times a month ',' never '. Statistical analysis was used in the form of descriptive frequency. This study found that the staple food category showed the highest consumption of white rice more than 1 times a day (80.4%). Fast food category showed the most consumption in instant noodles 1-3 times a week (35.9%). The meat category showed s the highest consumption in chickens 4-6 times a week (27.2%). Category of fish showed the most consumption in fresh fish 1-3 times a week (28%). Nuts category showed the highest consumption of 4-6 times a week in Tempe (34.3%) and tofu (33%). Vegetable category showed the most consumption for 1-3 times a week in spinach and watercress respectively by 35%. The category of fruits showed the highest consumption of oranges (34.8%) 1-3 times a month. Dairy product category showed the highest consumption for 1-3 times a month on ice cream (40.1%). Drink category showed the most consumption of fruit juice 1-3 times a week (32.2%). Finally, as many as 78.3% never consume supplements, but the most consumption of honey (19.9%) for 1-3 times a month. This study concludes that instant noodle consumption is relatively high while vegetables and fruits are not consumed daily. Then, chicken is more often consumed than fresh fish by college students in Malang city.